COVID-19 Assemblages
1 online resource (220 pages).
Keywords: This book documents and analyzes the effects of the COVID-19 pandemic through queer and feminist perspectives. A testament of dispossessions as well as a celebration of various forms of resilience, community building and critical responses, it chronicles the social history of queer and trans persons and women in South Asia and the diasporas. Through a creative and collaborative form of ethnographic writing, the book enters in conversation with the worlds of domestic helps, caregivers, cultural workers, students, sex workers and other precariously employed people. It examines the confining effects of the pandemic on the lived realities of many queer and trans individuals, the caste-oppressed and women across socio-economic backgrounds. The chapters in the volume piece together narratives of prejudice, hardship, self-expression and resistance from interviews, personal accounts, as well as poems and stories from activists, artists and other collaborators. The book pays particular attention to issues of power and asymmetrical relationships amidst COVID-19 and offers critiques to deepen the understanding of the uneven fault lines within which historically oppressed persons reside in South Asia. Exploring themes of migration, disability and sexual politics, this book is an essential reading for scholars and researchers of gender and sexuality studies, cultural studies, South Asian studies, sociology and social anthropology.